Rock-hewn Churches of the Village of Angua (Tigray, Ethiopia): The Monuments of Three Historical Epochs - Klyuev, Sergey A. (Actual Problems of Theory and History of Art, 2021)
The article is based on the results of a field study carried out with the financial support of the Russian Foundation for Basic Research in the fall of 2020. It has been devoted to the analysis of three rock-hewn churches created in different historical periods (including one modern monument) around the village of Angua, located in the mountainous region of Geralta (Tigray, Ethiopia). The text examines the characteristic features of the monuments, expounds the author’s position on their typological affiliation and dating, and describes their current state of preservation. These churches illustrate the three most important periods in the history of the Tigray region, during which one of the most active phases of the creation of rock-hewn churches has occurred. The article also examines the historical reasons behind these periods of construction activity.This research has been completed with the support of the Russian Foundation of Basic Research, project № 19-012-00299.
Keywords: rock-hewn churches; Ethiopia; Tigray; typology; attribution